Investigating Risk Factors for Kidney Stones in Department of Nephrology Saidu Teaching Hospital Swat - Shah Fahad, Mazhar Ul Haq, Muhammad Shahid, Syed Munib, Fazli Wahad (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The main objective of this study is to investigate the risk factors associated with kidney stones in the Department of Nephrology, Saidu Teaching Hospital, Swat, from Jan 2021 to Jan 2022. Specific objectives of this study are to: Identify and examine the demographic, medical and lifestyle factors of patients with and without kidney stones. Analyze the risk factors for the different types of kidney stones. Determine the relative risk of each risk factor for kidney stone formation. Make suggestions for prevention and management strategies of kidney stone development. Methods: This study was a retrospective case-control study in the Department of Nephrology, Saidu Teaching Hospital, Swat, from Jan 2021 to Jan 2022. Patient records from this period were reviewed and demographic, medical, and lifestyle factors of patients with and without kidney stones were compared. Risk factors for stone formation were determined using univariate and multivariate analyses. Statistical analysis was conducted using the chi-square test, Fisher’s exact test, and logistic regression. Results: A total of 193 patients of various ages had been admitted to the nephrology department from Jan 2021 to Jan 2022; 10 of these had a kidney stone. Of the kidney stone patients, six (60%) were male and four (40%) were female. The mean age of those with kidney stones was 43.6 years. Of the risk factors analyzed, male sex, family history of stone disease, diabetes, hypertension, and certain lifestyle factors such as drinking soft drinks and eating a diet high in animal proteins were significantly associated with stone formation. Conclusion: This study identified a number of risk factors associated with the formation of kidney stones in the nephrology department of Saidu Teaching Hospital between Jan 2021 to Jan 2022. Male sex, family history of stone disease, diabetes, hypertension, and certain lifestyle factors such as drinking soft drinks and consuming a diet high in animal proteins were found to be significantly associated with stone formation. Further research is needed to gain a better understanding of these risk factors and develop prevention and treatment strategies for kidney stone formation. Keywords: Kidney Stones, Risk Factors, Department of Nephrology, Saidu Teaching Hospital